2020
DOI: 10.3390/ani10030449
|View full text |Cite
|
Sign up to set email alerts
|

Defatted Rice Bran Supplementation in Diets of Finishing Pigs: Effects on Physiological, Intestinal Barrier, and Oxidative Stress Parameters

Abstract: Simple Summary: Most studies on dietary fiber mainly focus on the digestibility of feed nutrients and microbial flora, etc. However, insufficient attention has been paid to the regulation of immune and oxidative stress of the intestinal tract by dietary fiber. This study investigated the effects of varying levels of defatted rice bran replacing corn on physiological, intestinal barrier, and oxidative stress parameters in finishing pigs. Based on the current findings, a high diet of rice bran will not only redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…The permeability of the intestinal barrier plays an important role in gut health (Gosain and Gamelli, 2005;Bischoff et al, 2014), and barrier function is correlated with antioxidant activity, inflammatory response, and immune function in the intestine (Zhou et al, 2017b;Wang et al, 2018;Fan et al, 2020). In the present study, glucose oxidase supplementation maintained the shape and regularity of intestinal villi and reduced DAO levels in broilers fed moldy corn, thereby demonstrating beneficial effects on intestinal integrity.…”
Section: Discussionsupporting
confidence: 56%
“…The permeability of the intestinal barrier plays an important role in gut health (Gosain and Gamelli, 2005;Bischoff et al, 2014), and barrier function is correlated with antioxidant activity, inflammatory response, and immune function in the intestine (Zhou et al, 2017b;Wang et al, 2018;Fan et al, 2020). In the present study, glucose oxidase supplementation maintained the shape and regularity of intestinal villi and reduced DAO levels in broilers fed moldy corn, thereby demonstrating beneficial effects on intestinal integrity.…”
Section: Discussionsupporting
confidence: 56%
“…Accumulated studies have shown that BR has a similar AA digestibility to corn in broilers [37]. A study reported that feeding rice instead of corn increased nutrients digestibility and growth performance in pigs [41,42]. BR has a higher Met, Ser, and Tyr content than rice in our study.…”
Section: Discussionsupporting
confidence: 55%
“…Rice bran, a co-product obtained during rice milling process, is rich in cell wall materials such as hemicellulose and cellulose containing neutral detergent fiber in the range of 19-34% (192,193). The high fiber content is a major limitation of its use in young animal diets especially in newly weaned pigs.…”
Section: Fermented Rice Bran Extractsmentioning
confidence: 99%